2010
DOI: 10.1038/ejcn.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional care routines in Italy: results from the PIMAI (Project: Iatrogenic MAlnutrition in Italy) study

Abstract: Background/Objectives: Disease-related malnutrition is a common comorbidity at hospital admission. The purpose of the present report was to describe the data on nutritional care routines collected during the Project: Iatrogenic MAlnutrition in Italy (PIMAI) study, as these may be helpful to avoid iatrogenic malnutrition and improve nutritional policies. Subjects/Methods: Standards of nutritional care were assessed on the basis of (1) adherence to study protocol (completeness of data collected); (2) attitude in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
4
11
0
1
Order By: Relevance
“…Our results also paralleled those observed by others noting that low MNA scores predict poor outcomes in geriatric hospitalized patients [37]. While this was not surprising, the fact that the relationship was not modified by PA at 48 months suggests that both could potentially be biomarkers for death in this at-risk population, at least in the long run.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also paralleled those observed by others noting that low MNA scores predict poor outcomes in geriatric hospitalized patients [37]. While this was not surprising, the fact that the relationship was not modified by PA at 48 months suggests that both could potentially be biomarkers for death in this at-risk population, at least in the long run.…”
Section: Discussionsupporting
confidence: 90%
“…Various studies have estimated that about 30-50% of critically ill patients have clinical evidence of malnutrition. [9101112] These studies have also reported that the nourishment status of ICU patients generally deteriorates during the stay at the hospital, possibly due to inadequate nutritional supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Along with this, as previously reported for the Geriatric Nutritional Risk Index (GNRI) tool [10], the MNA seems to describe the potential patient's 'journey' across the different healthcare settings. In addition, also the poor nutritional routines and attitudes among healthcare professionals may be involved in the process of nutritional deterioration [122]. This need significantly increases in those admitted to hospitals.…”
Section: The Picture Of Nutritional Status According To the Mini Nutrmentioning
confidence: 99%